Efektivitas Bantuan Hukum Gratis bagi Masyarakat Miskin di Wilayah Hukum Pengadilan Negeri Gresik (International Forum of Researchers and Lecturers, 2024)
Access to justice is a fundamental right of every citizen, yet the poor often face barriers in obtaining legal aid. This study aims to analyze the implementation and effectiveness of free legal aid in the jurisdiction of the Gresik District Court. This study uses a mixed methods approach, with data collection methods including interviews, surveys, observations, and document studies. The results show that most of the poor in Gresik do not understand the procedures and requirements for obtaining free legal aid. In addition, the effectiveness of free legal aid is also influenced by factors such as service quality, availability of information, and coordination between institutions. This study provides recommendations to improve the effectiveness of free legal aid, including through increased socialization, simplification of procedures, improvement of service quality, and strengthening coordination between relevant institutions. This study is expected to contribute to improving access to justice for the poor in Indonesia.